Biomechanical Study of Syndesmotic Stability in AITFL and PITFL Injury Models. Issue 4 (November 2022) - Takahashi, Katsunori; Teramoto, Atsushi; Murahashi, Yasutaka; Shiwaku, Kosuke; Nabeki, Shogo; Kamiya, Tomoaki; Watanabe, Kota; Yamashita, Toshihiko
Category: Basic Sciences/Biologics; Trauma Introduction/Purpose: Severe ankle syndesmotic injuries can cause not only anterior inferior tibiofibular ligament (AITFL) injury but also posterior inferior tibiofibular ligament (PITFL) injury. However, the biomechanical stability and the best surgical treatment method for PITFL injuries are unknown. This study aimed to evaluate the stability of AITFL and PITFL injury models and the treatment models with suture-button (SB) fixation, AITFL augmentation with suture-tape (aST), and PITFL augmentation with suture-tape (pST). We hypothesized that PITFL injury causes posterior instability of syndesmosis and that this can be stabilized with pST fixation Methods: This study was approved by our institution's ethics review board. Ten normal fresh-frozen cadaver legs (4 males and 6 females) that were donated to our university's department of anatomy were used. The specimens were tested with the application of traction and rotational forces for dorsiflexion and external and internal rotation of the ankle joint. The fibular rotational angle related to the tibia (FRA), anterior tibiofibular diastasis (aTFD), and posterior tibiofibular diastasis (pTFD) were measured using the magnetic tracking system. Intact, injured (AITFL, PITFL and IOM resection), SB fixation, SB + aST fixation, and SB + aST + pST fixation models were made and loaded with forces. One-way ANOVA was used to evaluate the relationship between the models. Post-hoc analysis of the differences between the models was performed using Dunnett's test. A p value of 0.05 was chosen as the level of significance. Results: In the injured model, both FRA and TFD were significantly increased compared with those of the intact model in all directions. In the SB fixation model, only FRA with an external rotation force was significantly increased compared with that of the intact model. In the SB+aST model, both FRA and aTFD were not significantly different from those in the intact model. Conclusion: The results of this study showed that there was external and internal rotational instability in the AITFL and PITFL injury models, while there was stability in the SB + aST model. SB fixation alone did not reduce FRA with an external rotation force and there was no significantly different FRA with an internal rotation force. With SB fixation alone, anterior instability was found to be greater than posterior stability, while aST fixation was associated with anterior stability. In this study, the change in syndesmosis stability after pST fixation was found to be restrictive.